Feeding Monensin to yearling cattle on summer grass - F. Schwartz; E. Smith; Jack G. Riley; L. Corah (Kansas Agricultural Experiment Station Research Reports, 1977)
Two grazing trials conducted at different locations in Kansas evaluated feeding Monensin to grazing yearling cattle. In one trial Monensin was fed with and without implant treatments of diethylstilbestrol or Ralgro. Monensin increased weight gain on summer grass; diethylstilbestrol and Ralgro implants also increased weight gains, and the combination of Monensin with either implant was more effective than Monensin alone.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Monensin; Yearling cattle; Weight gain